UPAYA MENINGKATKAN PRESTASI BELAJAR READING DENGAN MODEL PEMBELAJARAN KUANTUMPADA SISWA KELAS XII IPA 7 SEMESTER 2 SMA NEGERI 2 DENPASAR TAHUN AJARAN 2017/2018 - Adnyana, I Wayan Suarka (Jurnal Santiaji Pendidikan (JSP), 2019)
This research was carried out in Denpasar Public High School 2 in Class XII IPA 7, where students' learning achievement for reading material was quite low. The purpose of writing this class action research is to find out whether the Quantum Learning Model can improve student learning achievement. The data collection method is a learning achievement test. The data analysis method is descriptive. The results obtained from this study are Quantum learning models can improve student learning achievement. This is evident from the results of the learning completeness percentage obtained initially at 26.19%, in the first cycle it became 76.19% and in the second cycle it became 90.48%. The conclusion obtained from this study is that Quantum learning models can improve learning achievement.